Safe Search Engines To Protect Children And Negative Digital Content Reality And Rationalization Mechanisms - Bousnane , Rokia (المجلة الجزائرية للأمن الإنساني, 2022)
The aim of the research is to clarify one of the research priorities in ensuring that children use the Internet in an appropriate and safe manner, working to upgrade the level of this important group of society on which the future depends in construction and change, and it calls for learning the skills of research and analysis away from cyber threats, or inappropriate content The paper works to identify search engines that are better at examining websites harmful to children and adolescents when their filtering features are activated, and sets an important vision for facing the negative challenges posed by the digital space. extremism, with the need for parental and school support.